ORGANOLEPTIC PROPERTIES AND NUTRITIOUS CONTENT OF BISCUIT BASED ON LOCAL FOOD - Rosa Hadiana Putri; Anak agung Sagung Putri Chandradewi; Reni Sofiyatin; Made Darawati (poltekkes kemenkes mataram, 2018)
Abstract: Biscuits are bakery products made by baking. Local food ingredients in West Nusa Tenggara is potential to be utilized as the ingredients for making biscuits, for instance corn, soybeans, yellow pumpkins and katuk leaves (Sauropus androgynous). Preliminary trials used limited panellists, it was obtained the most delightful formulas were 12 g of corn flour, 12 g soy flour, 12 g pumpkin flour, and 5 g katuk leaves flour. The objective study was to identify the organoleptic properties and nutritious content of biscuits based on local food. The methods was experimental research in laboratory by using Completely Randomized Design of single factor with addition of 25%, 30% and 35% soybean flour. Assessment of organoleptic properties utilized trained panelists somewhat and consumers. The addition of soybeans to biscuits had a significant effect on the texture and taste of biscuits. The results of the color assessment employed panelists are somewhat trained 3.12 - 3.46; Scent assessment 3.28-3.52; Texture assessment 3.14-3.68 and taste assessment 3.40-3.76. The result of color assessment used consumer panelist 4.24-4.4; Scent assessment 4.2; texture assessment 4.8-5 and taste assessment 3.2-4.2. Biscuits contain 469,415 kcal, 13,815% protein, 21,815% fat, 54.455% carbohydrate, 6.49% water, and 3.44% ash. The best treatment is a biscuit with 25% added soybean flour (t1).Keywords: Biscuits; Nutrient Content; Organoleptic Properties.